2011
DOI: 10.1210/jc.2011-0031
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Accumulation Product Is Associated with Impaired Glucose Tolerance in PCOS Women

Abstract: LAP is an easily obtainable and cheap marker associated with IGT in PCOS and control women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 20 publications
9
70
0
1
Order By: Relevance
“…This notion is supported by our finding showing a strong correlation of VAT and trunk located fat layers with FLI, whereas leg fat layers were inversely correlated with FLI. Of note, high levels of lipid accumulation product reflecting increased abdominal fat deposition are higher in PCOS than in BMI-matched control women and have been linked to IGT in PCOS women (32). Interestingly, PCOS women with a fatty liver have increased preperitoneal, mesenteric, and subcutaneous fat as well as an increased intima-media thickness (33), which is in line with our data showing a correlation of FLI with an adverse metabolic profile.…”
Section: Discussionsupporting
confidence: 89%
“…This notion is supported by our finding showing a strong correlation of VAT and trunk located fat layers with FLI, whereas leg fat layers were inversely correlated with FLI. Of note, high levels of lipid accumulation product reflecting increased abdominal fat deposition are higher in PCOS than in BMI-matched control women and have been linked to IGT in PCOS women (32). Interestingly, PCOS women with a fatty liver have increased preperitoneal, mesenteric, and subcutaneous fat as well as an increased intima-media thickness (33), which is in line with our data showing a correlation of FLI with an adverse metabolic profile.…”
Section: Discussionsupporting
confidence: 89%
“…(triglycerides (TG) (mmol/l)). Elevated LAP was defined as O44.1 as described previously in a large PCOS cohort as best cut-off for detecting disturbed glucose tolerance (8). VAI was calculated using the formula ðWC ðcmÞ=ð36:58…”
Section: Methodsmentioning
confidence: 99%
“…This notion is supported by a study among 469 South Asian PCOS women with increasing MS prevalence from the lowest (6.7%) to highest (42.0%) quartiles of BMI and a relatively high overall prevalence of 36%. Further, central obesity and visceral fat accumulation have been associated as key factors in the development of the MS, and the prevalence of the MS is low if there is no excessive abdominal adiposity (8,9). Moreover, non-alcoholic fatty liver disease (NAFLD) is considered the hepatic manifestation of MS and it has been shown that 89% of PCOS women with MS have elevated fatty liver index indicating NAFLD (24).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 2 more Smart Citations